Service Quality of Lubuklinggau Prison - Yohanes Susanto; R.A Rodia Fitri Indriani (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2024)
This research aimed to determine the service quality, competency formation of officers, supervision, and motivation in Lubuklinggau Class II a Prison South Sumatra, Indonesia. The population and sample were 66 respondents from prison officers. This research used a qualitative descriptive approach. Based on the results on the perception of service quality, officers have provided services in the tangible (physical evidence), reliability, response, assurance (guarantee), and empathy aspects. This is in line with the survey on the perception of service quality with a score of 1.357 or in the good category, perception of competency with a score of 1.300 meaning in a good category supported by an increasing competency due to training and opportunities to continue formal education, on the perception of supervision with a score of 1.356 meaning in good category and on the perception of motivation with a score of 1.085 meaning motivation given by managers to officers in the good category. Of the four dimensions above, the dominant score was on the service quality aspect, so it is recommended to increase the service quality for prisoners and detainees in Lubuklinggau Class II a Prison to meet the needs that have been overcapacity